Power quality and supply interruption studies at selected location of ITM multi-storey and engineering buildings / Abdullah Abdul Rahman - Abdul Rahman, Abdullah (1995)
The introduction of modern technology incorporating the use of non linear loads and rapid rise in demand of electricity has contributed to the rise in power related problem. The growth of power related problem can be directly linked to the growth of computer based loads and it is the intention of this studies to certify the above mentioned phenomena towards the power problem in ITM. The electrical utility has long be viewed as the major source of power disturbance and this is not generally true. Electrical problem within the facility such as aged wiring, malfunction protective device, poor discrimination of protection system, large switching loads do contribute to the power disturbance apart from the stress placed upon the electrical system by the non linear loads. It is the intention of this studies to determine the power quality and the cause of supply interruption that occurs in ITM. The site chosen to conduct this studies were based on immediate requirement by the relevant departments and the high frequency of supply interruption. Two major sites chosen are multi storey supply system to level 9 and Engineering Block A. This studies are classified under the category of parameter identification and data collection.